2018
DOI: 10.1017/s0021859618000333
|View full text |Cite
|
Sign up to set email alerts
|

Screening for soybean varieties suited to Belgian growing conditions based on maturity, yield components and resistance to Sclerotinia sclerotiorum and Rhizoctonia solani anastomosis group 2-2IIIB

Abstract: Policy makers and farmers in north-west Europe are expressing a growing interest in soybean production. However, cool and wet climatic conditions in this region pose challenges for this crop in terms of reaching maturity and producing sufficient yield and create additional disease pressure from the fungal pathogens Sclerotinia sclerotiorum and Rhizoctonia solani. To increase the chance for successful introduction of this new crop in Belgium and to determine the main issues for local soybean breeding programmes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 27 publications
(40 reference statements)
0
28
0
Order By: Relevance
“…These scenarios are consistent with observed and recommended soybean frequencies in crop sequences in Europe. Indeed, a 1-in-3 year or 1-in-4 year soybean cultivation is often recommended to limit the risk of disease occurrence 33 (especially those caused by two fungal pathogens Sclerotinia sclerotiorum and Rhizoctonia solani 34,35 ), although higher frequencies are observed in Europe 33,36 and other countries 37,38 . Third we assumed that soybean is grown preferably in high-yielding grid-cells.…”
Section: Resultsmentioning
confidence: 99%
“…These scenarios are consistent with observed and recommended soybean frequencies in crop sequences in Europe. Indeed, a 1-in-3 year or 1-in-4 year soybean cultivation is often recommended to limit the risk of disease occurrence 33 (especially those caused by two fungal pathogens Sclerotinia sclerotiorum and Rhizoctonia solani 34,35 ), although higher frequencies are observed in Europe 33,36 and other countries 37,38 . Third we assumed that soybean is grown preferably in high-yielding grid-cells.…”
Section: Resultsmentioning
confidence: 99%
“…Together with understanding the sources of variation, knowing the strength and direction of relationships among different traits is of great value for breeding programmes as it enables the enhancement of more than one trait at the same time. Although significantly negative relationship between oil and protein content was reported in most researches [61,70,81,84], in the research analysing variations from 21 studies conducted over 15 years (2002-2017), Assefa et al [142] concluded that, when pooling data across all studies, there was no significant relationship between oil and protein content, but a tendency for a negative relationship was observed when plotting data separately for each of the studies evaluated in the database. Furthermore, oil content increased slowly with yield increase suggesting a positive relationship, but when relationships were investigated by study, 63% of studies supported a positive relationship, and the other 37% displayed a slightly negative relationship between seed yield and oil content [142].…”
Section: Oil Content and Fatty Acid Compositionmentioning
confidence: 98%
“…Such contradictory reports are a major concern in plant breeding since they complicate decision-making process during selection. Breeding for increased protein content is further complicated by negative correlation between protein content and yield reported by many authors [70,78,79], although there are studies indicating no significant correlation between those two parameters [80,81]. Furthermore, Vollmann et al [61] suggested that even moderately negative correlation between seed protein content and seed yield, means the selection of breeding lines with both improved protein content and acceptable yield level should be possible.…”
Section: Protein Content and Amino Acid Compositionmentioning
confidence: 99%
See 2 more Smart Citations